Design of mobile robot in agriculture : development and analysis of mobile robot body frame structure against applied load - Mohd Rezykin Md Shariff (2019)
This report is about carrying out project “Design of Mobile Robot in Agriculture: Development and Analysis of Mobile Robot Body Frame Structure Against Applied Load”, which is specially intended to kick of the main project which is to develop a mobile robot which specialized for agriculture sector activities. On carrying out the project there are several information data and information need to be extracted from journals and research papers in order to ideate the methodological process on analysing the mobile robot frame structure. On talking about mobile robot in other industries, there are few parameters which are significantly different on the field of study of mobile robot in agriculture climate such as the different parameters and requirement due to the implementation of robotic activities in the outdoor which is known to the appearances of water and moist which will have affected some or most of the mechanical and electronics part of the mobile robot. The idea or motivation on kicking off this project is to carry a social mission which is to aid the farmers in level of groups varied from the small scale farmers up until large scale farmers in order to cater the demand on foods on agriculture industries which is known widely the climate problem which is the request or demand on food percent is higher from the production. This due to several aspects such as labour shortage or the dumping of unskilled workers which worsen the situation. From this two issues, the problem had been deepened research to find out the factors of labour shortage which is seen as with the modernization era of technology especially in robotic which is proven capable of aiding human in their task, able to take role to fulfil this humanity mission. In the end, the project will be carried out from idea of this first paper which is the conceptual of the mobile robot and in the future the research able to expand to the wide research of the mobile robot for the agriculture activity. The project started with conducting a study and research from journals and research papers on information regarding mobile robot development concept and parameters especially for agriculture mobile robot. The study also consists of extracting and comparing design from other journal and research papers in order to interpreted it into concept design for this project mobile robot. Other than that, method on analysis for the mobile robot body structure also included in the research to find out how to carry out experiment which to test the strength of the structural body. The analysis which will involve in this project is by carrying out stress analysis by using Finite Element Analysis software which is embedded in the design software to observe the body stress or pressure grenerated which lead to fracture once a value of load applied to the body. At the same time to compare between two materials, which are mild steel and stainless steel grade 440c to determine which materials gives better strength to be set on developing the structure for the mobile robot. Once all the information and conceptual design obtained, the design will go through a sketch conceptual design and at then later on the sketch design was translated in 3d form drawing. The purpose of translating is to carry out strength analysis for the structural body to determine if the designed body capable of supporting loads which up to 30kgs of load. On the analysis method, the load was applied by stages which is starting with 10kg load, then continue by 1okgs until 30kgs load to observe the increment of pressure and at the same time to oberve on the simulation result the most fracture part from the load applied. This analysis was carried out twice for differeent materials as mention before to determine which materials gave a better strength to be chosen to develop the body structure. Result shows that stainless steel gave better result in term of strength against load applied but eventually on deciding to finalize the material selection for the structural body, there is no there is no final answer for this paper because the purpose of this project is to find out which materials gave strength, but in order to finalize the selection there are several more parameters need to be count in such as material fabrication and finishing costing etc.